2007
DOI: 10.1111/j.1440-1746.2007.04905.x
|View full text |Cite
|
Sign up to set email alerts
|

Butter feeding enhances TNF‐α production from macrophages and lymphocyte adherence in murine small intestinal microvessels

Abstract: T-lymphocyte adherence to microvessels of the small intestinal mucosa was significantly enhanced after butter ingestion. This enhancement is due to increase in expression levels of adhesion molecules of the intestinal mucosa, which is mediated by TNF-alpha from macrophages in the intestinal lamina propria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 43 publications
(74 reference statements)
0
35
0
Order By: Relevance
“…Simultaneously, the intracorneal expression of antiangiogenic molecules, such as TSP-1, TSP-2, and ADAMTS-1, was enhanced after alkali injury, and the increase was attenuated by Cl2MDP-lip. Because macrophages are the source of angiogenic factors, including MMP-9 30-31 and TNF-a, 32,33 and antiangiogenic factors, including ADAMTS-1, TSP-1, and TSP-2, 13,34-36 depletion of macrophages as a whole may result in decreased expression of both proangiogenic and antiangiogenic molecules in a balanced manner.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the intracorneal expression of antiangiogenic molecules, such as TSP-1, TSP-2, and ADAMTS-1, was enhanced after alkali injury, and the increase was attenuated by Cl2MDP-lip. Because macrophages are the source of angiogenic factors, including MMP-9 30-31 and TNF-a, 32,33 and antiangiogenic factors, including ADAMTS-1, TSP-1, and TSP-2, 13,34-36 depletion of macrophages as a whole may result in decreased expression of both proangiogenic and antiangiogenic molecules in a balanced manner.…”
Section: Discussionmentioning
confidence: 99%
“…Butter administration significantly increased TNF-␣ in the lamina proprial macrophages [135] BALB/c mice LF: 10% kcal fat; high omega-3 (n-3): 40% kcal fat For evaluating the effects of parental diet, littermate mice were placed on either LF or n-3 diet one day before being placed in cages. Offspring mice were exposed to these diets until birth, and for another 3 weeks via breast feeding.…”
Section: Referencementioning
confidence: 99%
“…Most studies shown in Table 4 have focused on the impact of mixtures of fat and fatty acids, the specific types of fat may be relevant, as different types may have varying impacts on immune status. For example, unsalted butter rich in saturated fatty acids may upregulate inflammatory status by influencing proinflammatory cytokines [135]. However, a maternal high fat diet rich in omega-3 polyunsaturated fatty acids can down-regulate inflammation status and modulate immune function in mice offspring, by modulating the balance of proinflammatory and anti-inflammatory cytokines [136].…”
Section: Referencementioning
confidence: 99%
“…The fact that the proinflammatory factors such as histamine, TNF-α and interleukins (e.g. IL-8, IL-13) that are found to be produced in excessive amounts in IBD [49] are also produced during active fat absorption [8,9] raises the possibility that chronic ingestion of a high-fat diet may initiate the release of these proinflammatory factors by mast cells as well as by other immune cells. Thus, it is not surprising to find numerous reports linking chronic consumption of high fat and the increased incidence of IBD [11,12,48,49].…”
Section: Significance Of the Nutrient-induced Intestinal Inflammationmentioning
confidence: 99%
“…For instance, it has been reported that acute duodenal feeding or long-term consumption of fat (e.g. olive oil or saturated butter fat) increases lymphocyte trafficking in rat intestinal lymph [7], and increased production of cytokines like tumor necrosis factor-α (TNF-α), interferon or interleukin 6 (IL-6) by macrophages [8], intraepithelial lymphocyte [9], and intestinal epithelial cells [10]. These observations are further extended by our recent findings that a duodenal infusion of liposyn II, a lipid emulsion containing mainly polyunsaturated fatty acids (PUFAs) activated intestinal mucosal mast cells (MMC) resulting in the release of various mast cell mediators such as histamine, protease [rat mast cell protease II (RMCPII)], as well as the lipid mediator prostaglandin D 2 (PGD 2 ) into intestinal lymph (unpublished data).…”
Section: Introductionmentioning
confidence: 99%